Investigation of a Crime Scene with Two Victims and a Perpetrator Through DNA Traces - Andrade, M. A. P.; Ferreira, M. A. M. (EasyChair Preprint Nº 7897, 2025)
To deal with crime identification problems, that are examples of situations in which forensic approach the DNA profiles is frequent, it is needed an introduction to present and explain the various concepts involved. So the use of object-oriented Bayesian networks (OOBN), examples of probabilistic expert systems (PES), is shown and exemplified